Working capital financing by banks in small enterprises: Problems and challenges for Bangladesh - Hossain, Md Mosharref; Ibrahim, Yusnidah (IGI Global, 2020)
Among all the economic players, small enterprises (SEs), by number, dominate the whole world business segment. However, it is a very common problem for SEs, in every economy either developed or developing, to get access into formal financial sector. Working capital can be treated as the life blood for SEs to be operated. But unfortunately, most of the small enterprises face serious problem while obtaining such loan from banks. On the other hand, banks face a lot of problems to finance working capital to SEs. Therefore, this chapter intends to identify the problems faced by SEs in obtaining and by banks while financing working capital. A total of 413 small enterprises were interviewed through a structured questionnaire administrated directly by the researchers and selected purposively from the capital city (Dhaka) of Bangladesh. The major findings indicate that about 72% small enterprises got the access into banks for working capital loan although all of them face a lot of problems while obtaining such loan from banks. To identify the problems and challenges faced by banks while financing working capital to SEs, 34 commercial banks' officials working in SME department were interviewed through questionnaire and selected purposively based on their high involvement into SME sector lending. Bankers encountered different problems and challenges related to working capital financing in SEs. Based on the survey findings, a good number of solutions have been formulated for policy initiatives.